Optical Kerr effect in Q-switched neodymium(lll): doped silica fibre laser - Hooi, Y. C.; Ahmad, H. B. (Malaysian Journal of Science, 1995)
Operating characteristics of Q-switched Nd3+: doped single mode silica fibre with a mechanical chopper as a Q-switching device are presented. Peak power as high as 16 W with pulse duration 146 ns are demonstrated. Self-mode-locking in Nd3+:doped fibre is also reported. Output power of 312 W with centre pulse duration of 4 ns is observed.